Containing of biomaterials based on chitosan and argenium (I) nitrate - Stepura N. O.; Sklyar A. M. (Zenodo, 2018)
Great interest in chitin and chitosan is due to their unique physiological and environmental properties, such as biocompatibility, biodestruction, physiological activity, and others. The article demonstrates the possibility of obtaining chitosan biomaterial from Antarctic krill. To this end, the task was set for the development of technology for the obtaining of chitin from primary raw materials. Physicochemical parameters of the quality of chitosan obtained from the Antarctic krill armor were studied. Based on the analysis performed and comparison of the properties of the samples, it was established that our biomaterial, chitosan iodide with silver (I) nitrate, is close to chitosan.